Muslim Character Values in Cartoon Sulukiyyat Al-Muslim Al-Shaghir Based on Roland Barthes’ Semiotic Perspective - Munawwarah, Madinatul; Yurisa, Penny Respati (Institut Agama Islam Negeri Curup, 2023)
This study aims to reveal the denotation and connotation levels in cartoon Sulukiyyat al-Muslim al-Shaghir based on Roland Barthes' semiotic perspective and to reveal the values of Muslim character in that cartoon. This article is motivated by the phenomenon of people who are less concerned or even apathetic about the surrounding environment even though they live in an Islamic majority environment. This research type is qualitative. The data are taken from the cartoon Sulukiyyat al-Muslim al-Shaghir produced by Caartonile on YouTube. The data are collected using the watch and note technique. The data are validated by increasing persistence and discussing them with peers and experts. The data are analyzed using descriptive analysis techniques consisting of data presentation, data analysis, and conclusion drawing. The results show that the Muslim character values in cartoon Sulukiyyat al-Muslim al-Shaghir based on Roland Barthes' theory at the denotation and connotation levels are moral and social values. Moral values consist of four, namely ethics of giving advice, ethics of speaking, ethics of visiting, patience, and forgiveness. In the meantime, social values consist of three, namely respecting elders, not being wasteful, and maintaining public facilities.